THE The Correlation Between Vocabulary Mastery and Writing Skill a Meta-Analysis - Kristi Hema Bina Br Barus; Nelson Balisar Panjaitan (Pendidikan Bahasa Inggris Universitas Nurul Huda, 2022)
This Meta-Analysis turned into carried out to synthesize statistics throughout comparable research. This studies hired a descriptive qualitative approach. The facts of this look at turned into 28 comparable research that centered at the writing talent that concerned 993 samples. The facts contained r and n. r is a coefficient price and n are respondents. In gathering the facts, the researchers used 5 steps, namely: Collecting research or meta-evaluation materials; Calculating the impact length of every look at; Estimating the precis impact or suggest impact length; Moderator variable evaluation; Publication bias evaluation. The software program that turned into applied to research the facts turned into JASP. Since K= 27, so 5K+10 = 145. The fail-safe N value obtained is 2437.000, with a significant target of 0.05 and p < 0.001. Because of the safe value of N > 5K+10, it can be concluded that there is no publication bias problem in the meta -analysis study.